2009
DOI: 10.1007/bf03218632
|View full text |Cite
|
Sign up to set email alerts
|

Charge carrier photogeneration and hole transport properties of blends of a π-conjugated polymer and an organic-inorganic hybrid material

Abstract: This study examined the charge carrier photogeneration and hole transport properties of blends of poly (9-vinylcarbazole) (PVK), a π-conjugated polymer, with different weight proportions (0~29.4 wt%) of (PEA)-VOPO 4 ·H 2 O (PEA: phenethylammonium cation), a novel organic-inorganic hybrid material, using IR, UV-Vis, and energy dispersive spectroscopy (EDS), thermogravimetric analysis (TGA), steady state photocurrent (SSPC) measurement, and atomic force microscopy (AFM). The SSPC measurements showed that the pho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 43 publications
0
4
0
Order By: Relevance
“…In the literatures, a series of carbazole-based molecules have been demonstrated as excellent hole transporting materials in past decades. [55][56][57] Therefore, it is believed that the 2PACz could ameliorate the hole transport in BHJ with the low-donor-content. Space charge-limited current (SCLC) measurements were implemented to investigate film hole (μ h ) and electron (μ e ) mobilities perpendicular to the substrate plane.…”
Section: Charge Generation Recombination and Extractionmentioning
confidence: 99%
“…In the literatures, a series of carbazole-based molecules have been demonstrated as excellent hole transporting materials in past decades. [55][56][57] Therefore, it is believed that the 2PACz could ameliorate the hole transport in BHJ with the low-donor-content. Space charge-limited current (SCLC) measurements were implemented to investigate film hole (μ h ) and electron (μ e ) mobilities perpendicular to the substrate plane.…”
Section: Charge Generation Recombination and Extractionmentioning
confidence: 99%
“…37 Since the lowest unoccupied molecular orbital (LUMO) level of TPBi (2.7 eV) is situated between those of PVK (2.2 eV) and Ir(mppy) 3 (3.0 eV), the TPBi molecules diffused into the EML might have acted as the electron trap site. 39 In addition, Fig. 4b displays that the decrease in the current efficiency coincides with increasing NC.…”
Section: Resultsmentioning
confidence: 88%
“…It is frequently used as a polymeric host material in photovoltaic devices [3][4][5]. Recently, much work is being done on exploring the photoconductivity of PVK [6][7][8][9][10][11][12][13][14], yet a few have been reported that deal with the use of PVK as the polymeric host material where the polymer offers very poor efficiency [5,[15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%